The Impact of Global Transcriptional Regulation on Bacterial Gene Order - Yubero, Pablo; Poyatos, Juan F. (iScience, 2020)
Bacterial gene expression depends on the allocation of limited transcriptional resources provided a particular growth rate and growth condition. Early studies in a few genes suggested this global regulation to generate a unifying hyperbolic expression pattern. Here, we developed a large-scale method that generalizes these experiments to quantify the response to growth of over 700 genes that a priori do not exhibit any specific control. We distinguish a core subset following a promoter-specific hyperbolic response. Within this group, we sort genes with regard to their responsiveness to the global regulatory program to show that those with a particularly sensitive linear response are located near the origin of replication. We then find evidence that this genomic architecture is biologically significant by examining position conservation of E. coli genes in 100 bacteria. The response to the transcriptional resources of the cell results in an additional feature contributing to bacterial genome organization. [Display omitted] •Cell physiology determines a global transcriptional regulatory program•Constitutive genes show a differential response to this global regulation•The most responsive constitutive genes are located near the origin of replication•Global transcriptional regulation acts as a gene position conservation force Microbiology; Microbial Genetics; Mathematical Biosciences